Два новых для Палеарктики рода комароа-лимониид (Diptera, Limoniidae) и два новых вида этих родов - Савченко, Е.Н. (Вестник зоологии, 1980)
Two nearctic genera of the Limoniid-flies — Gonomyodes Al. and Hesperoconopa
Al.— are first recognized in the Palearctic. The first is represented in the local fauna by
G. (s. str.) similissima Sav., sp. n. (North Tien-Shan), the second — by H. acutistyla Sav. sp. n. (Southern Kuril islands, island Kunashir). Both of the new species are described and their male hypopygia are figured. The type-specimens are preserved in the collection of the Institute of Zoology in Kiev.